Model of Green Human Resources Behavior Based on Green Behavior Training, Green Competence, and Affective Commitment on Green Value - Marno Nugroho; Budhi Cahyono; Rifqi Hasa Gunawan (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2022)
This study used fundamental research to explore the concept of green management in behavioral theory. This study used 100 employees of PT Sidomuncul as respondents and used a purposive sampling method and multiple regression analysis for data analysis. The results of this study indicate that green behavior training has a positive and significant effect on green competencies. Green behavior training has a positive and significant effect on the affective commitment to green values. Green behavior training, green competencies, and affective commitment to green values have a positive and significant effect on human resources' green behavior. Green competencies and affective commitment to green values are the intervening variables between green behavior training and human resources green behavior. This study examines the antecedents and consequences of the green human resource management (HRM) model with the behavioral theory that explores green competencies and affective commitment. This research will contribute to increasing employee awareness to change their behavior towards green HRM. For social implications, this study provides a social impact of becoming a greener society environment.